A review and estimate of time spent in prison by offenders sentenced for murder - Nafekh, Mark; Flight, Jillian I. (Research Brief (Canada. Correctional Service Canada. Research Branch), 2002)
The purpose of the present study is to determine the average time offenders sentenced for murder spend in prison over three legislatively-relevant time periods : pre-1961 (pre-capital/non-capital murder sentences); 1961 to 1976 (capital/non-capital murder designation) and 1976 to 2002 (1st and 2nd degree murder designation)